Livestock guinea pigs in Ecuador as reservoirs of zoonotic protozoa and helminths - Salas-Rueda, Mauricio Xavier; Garnica-Marquina, Froilan Patricio; Curipoma-Maisincho, Verónica Patricia; Chávez Toledo, Katherine Natalia; Rocano-Marcatoma, Erika Carolina; Orlando, Solon Alberto; Arcos Alcivar, Fabricio; Rodriguez-Pazmiño, Angel Sebastian; Hermoso de Mendoza, Javier; Garcia-Bereguiain, Miguel Angel (Frontiers in Veterinary Science, 2025)
Guinea pigs (Cavia porcellus) are bred as laboratory animal models and pets worldwide. However, they are also raised as livestock in South American countries from the Andean region, including Ecuador. Despite their importance for the rural local economy, no specific management guidelines for guinea pig farming have been developed by Ecuadorian animal or public health authorities. Moreover, several reports have shown the carriage of diverse zoonotic pathogens in guinea pigs. In this study, the prevalence of enteric protozoan and helminths in guinea pigs from Ecuador was analyzed. Fecal samples from 765 guinea pigs from 153 farms were collected. The overall prevalence of parasitism was 86.0% (95% CI: 83.4–88.3). Five different genera of protozoan parasites, which include zoonotic species (Giardia, Cryptosporidium, Entamoeba, Eimeria, and Balantidium), were found, and the overall prevalence of protozoans was 56.21% (95% CI: 52.7–59.7). Seven different genera of helminth parasites, including zoonotic species Capillaria, Fasciola, Trichostrongylus, and Trichuris, were identified, with an overall helminth prevalence of 70.1% (95% CI: 66.8–73.2). Several risk factors related to animal production practices were considered and the multivariate analysis identified that forage based feeding, the use of wire cages and interaction with other domestic animals were associated with higher prevalence of parasitism. Our results highlight the role of guinea pigs as a reservoir for zoonotic enteric parasites of public health relevance in Ecuador. Moreover, our study is the first report of Fasciola hepatica in Ecuadorian guinea pig. Animal and public health guidelines from a One Health perspective must be implemented to prevent occupational exposure to parasites in guinea pig farming and to ensure food security in the Andean region, where this animal is a significant source of protein in the human diet.